2004
DOI: 10.1074/jbc.m409221200
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-activated Protein Kinase Regulation of Endothelial Cell Migration Depends on Urokinase Plasminogen Activator Expression

Abstract: The migration of endothelial cells in response to various stimulating factors plays an essential role in angiogenesis. The p38 MAPK pathway has been implicated to play an important role in endothelial cell migration because inhibiting p38 MAPK activity down-regulates vascular endothelial growth factor (VEGF)-stimulated migration. Currently, the signaling components in the p38 MAPK activation pathway and especially the mechanisms responsible for p38 MAPK-regulated endothelial cell migration are not well underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 56 publications
4
40
2
Order By: Relevance
“…Our studies are also in agreement with the previous studies demonstrating that Ang-(1-7) decreases the ERK signal transduction pathway in lung and prostate cancer cell growth arrest (10,16). A growing number of studies have shown that p38 MAPK-mediated cell migration and invasion (38)(39)(40)(41) pathways are involved in Ang II-stimulated migration of vascular adventitial fibroblasts in spontaneously hypertensive rats (42). A recent study demonstrated that the antimigration and anti-invasion effect of Ang-(1-7) was mediated through inactivation of the PI3K-Akt, p38 MAPK, and JNK signaling pathways (43).…”
Section: Discussionsupporting
confidence: 82%
“…Our studies are also in agreement with the previous studies demonstrating that Ang-(1-7) decreases the ERK signal transduction pathway in lung and prostate cancer cell growth arrest (10,16). A growing number of studies have shown that p38 MAPK-mediated cell migration and invasion (38)(39)(40)(41) pathways are involved in Ang II-stimulated migration of vascular adventitial fibroblasts in spontaneously hypertensive rats (42). A recent study demonstrated that the antimigration and anti-invasion effect of Ang-(1-7) was mediated through inactivation of the PI3K-Akt, p38 MAPK, and JNK signaling pathways (43).…”
Section: Discussionsupporting
confidence: 82%
“…Figure 3C and D also indicates that p38-MAPK blockade with SB202190 potently blocks spreading. We suggest that inhibition of spreading indirectly reduces matrix-induced RLC phosphorylation, but that the primary positive role of p38-MAPK during spreading is mediated via targets other than activation of RLC phosphorylation or myosin II contractility, possibly related to paxillin (35,36) or Plates were incubated in 37jC incubator for 1 hour and fixed with paraformaldehyde before photos were taken. B, quantification of spread area per cell, quantified via staining with Alexa 595-conjugated WGA and DAPI as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…The pyridinyl imidazole-sensitive p38 MAPK isoforms are often considered to be redundant enzymes, as their substrate specificities overlap significantly. However, in some cases these two isoforms have been shown to be able to discriminate between substrates, at least under conditions of forced overexpression of dominant-negative mutants (67,73).…”
Section: Discussionmentioning
confidence: 99%